2020
DOI: 10.1371/journal.pone.0239481
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum 25-hydroxyvitamin D levels with severe necroinflammatory activity and inflammatory cytokine production in type I autoimmune hepatitis

Abstract: 25-Hydroxyvitamin D [25(OH)D] has been reported to be associated with several chronic liver diseases. The relationship between 25(OH)D and autoimmune hepatitis (AIH) pathogenesis is incompletely understood. We investigated the association of serum total and free 25(OH)D levels with necroinflammatory activity and cytokine levels in 66 patients with AIH diagnosed in our hospital. The median age at AIH diagnosis was 57 years, and the male:female ratio was 7:59. The median serum total 25(OH)D level in therapy-naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(82 reference statements)
1
6
0
1
Order By: Relevance
“…A few studies have explored the relationship between AIH and vitamin D. Efe et al [ 92 ] found that mean vitamin D levels were significantly lower in 68 AIH patients than in controls (16.8 ± 9.2 vs. 35.7 ± 13.6, p < 0.0001) [ 4 ]. This finding was confirmed in a more recent study by Abe et al [ 93 ], in which they also highlighted that serum total vitamin D levels were significantly lower in patients with acute AIH than in those with chronic AIH (13.2 ng/mL vs. 16.0 ng/mL, p = 0.029). [ 3 ] A study showed that serum total vitamin D levels were significantly lower in patients with severe necro-inflammatory activity (12.4 ng/mL vs. 16.8 ng/mL; p = 0.0017) [ 93 ]; by contrast, levels of pro-inflammatory cytokines (IFN-γ and IL-33) were significantly higher in AIH patients with serum total Vitamin D levels of <15 ng/mL (IFN-γ: 0.21 vs. 0 pg/mL, p = 0.0181; IL-33: 26.54 vs. 13.13 pg/mL, p = 0.0036).…”
Section: Vitamin D In the Chronic Liver Diseasessupporting
confidence: 73%
See 1 more Smart Citation
“…A few studies have explored the relationship between AIH and vitamin D. Efe et al [ 92 ] found that mean vitamin D levels were significantly lower in 68 AIH patients than in controls (16.8 ± 9.2 vs. 35.7 ± 13.6, p < 0.0001) [ 4 ]. This finding was confirmed in a more recent study by Abe et al [ 93 ], in which they also highlighted that serum total vitamin D levels were significantly lower in patients with acute AIH than in those with chronic AIH (13.2 ng/mL vs. 16.0 ng/mL, p = 0.029). [ 3 ] A study showed that serum total vitamin D levels were significantly lower in patients with severe necro-inflammatory activity (12.4 ng/mL vs. 16.8 ng/mL; p = 0.0017) [ 93 ]; by contrast, levels of pro-inflammatory cytokines (IFN-γ and IL-33) were significantly higher in AIH patients with serum total Vitamin D levels of <15 ng/mL (IFN-γ: 0.21 vs. 0 pg/mL, p = 0.0181; IL-33: 26.54 vs. 13.13 pg/mL, p = 0.0036).…”
Section: Vitamin D In the Chronic Liver Diseasessupporting
confidence: 73%
“…Finally, three studies [ 92 , 93 , 94 ], found a correlation between low vitamin D levels and less probably response to therapy, with a higher number of patients needing a combination therapy (steroids + azathioprine) when Vitamin D levels were <15 ng/mL. These findings may correlate to vitamin D’s ability to promote the anti-inflammatory action of glucocorticoids [ 95 ].…”
Section: Vitamin D In the Chronic Liver Diseasesmentioning
confidence: 99%
“…Furthermore, five drugs (pioglitazone, medroxyprogesterone, dexamethasone, calcitriol, and rimonabant) have demonstrated therapeutic effects against liver diseases in clinical studies. Previous studies have also highlighted the therapeutic effects of dexamethasone and calcitriol on AIH ( Supplementary Table 6 ) [ 20 - 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identi ed calcitriol and dexamethasone as potential therapeutic agents for treating AIH. It is worth noting that vitamin D levels are signi cantly lower in patients with chronic-onset AIH (23). Moreover, corticosteroid regimens including dexamethasone are widely recognized as the standard treatment for AIH (24).…”
Section: Discussionmentioning
confidence: 99%